Profiling of Centella asiatica (L.) urban extract - Zainol, N. A.; Voo, S. C.; Sarmidi, M. R.; Aziz, R. A. (The Malaysian Analytical Sciences Society (ANALIS), 2008)

(untitled)
Centella Asiatica is one of those phytochemical that has been consume for hundreds years and it is claimed that the plant possess various healing effect and antioxidant properties. For many years, a lot of commercial and medicinal researches have been focusing their resources on this plant. Hence, the profiling of this plant is vital. This study was done to investigate the behaviour of active components in two different accessions commercially grown in Johore Bahru. Research procedures were carried out according to the modified method utilizing TLC and HPLC analysis method. The findings suggested that in different parts of Centella Asiatica contain different amount of phytochemicals. The highest concentration of phytochemicals was found in the second accession that was asiaticoside (2.56 ug/ml), madecasoside (5.30 ug/ml) and asiatic acids (3421.60 ug/ml). Leaves contain a higher concentration of those phytochemicals relative to the petioles and the roots.